Microstructure transition gradients in titanium dissimilar alloy (Ti-5Al-5V-5Mo-3Cr/Ti-6Al-4V) tailored wire-arc additively manufactured components - Kennedy, Jacob R.; Davis, Alec E.; Caballero Ramos, Armando; White, M.; Fellowes, Jonathan W.; Pickering, Ed J.; Prangnell, Philip B. (Elsevier, 2021)
The nature of the chemical mixing and microstructure gradients that occur across the interface transition, when manufacturing tailored components with the two high-performance dissimilar titanium alloys (Ti-6Al-4V (Ti-64) and Ti-5Al-5V-5Mo-3Cr (Ti-5553)) by the wire-arc additive manufacturing (WAAM) process, are reported. It has been shown that a relatively long-range chemical gradient occurs during the transition between layers produced with the two different titanium alloys, due to convective mixing in the melt pool between the substrate layers and new alloy wire. This resulted in a stepwise exponential decay composition profile normal to the layers, the width of which can be described by a simple dilution law, with steep local composition gradients seen within the boundary layers at the fusion boundary of each individual layer. The alloy-alloy composition gradients had little effect on the β-grain structure. However, they strongly influenced the transformation microstructure, due to their effect on the parent β-phase stability and the β → α transformation kinetics and reaction sequence. The microstructure gradient seen on transitioning from Ti-64 → Ti-5553 was significantly more abrupt, compared to when depositing the two alloys in the reverse order. Under WAAM thermal conditions, Ti-64 appears to be more sensitive to the effect of adding β-stabilising elements than when Ti-5553 is diluted by Ti-64, because at high cooling rates, stabilisation of the β phase readily suppresses α nucleation when cooling through the β transus, and the normal Ti-64 lamellar transformation microstructure is abruptly replaced by finer scale α laths generated by precipitation during subsequent reheating cycles.
Keywords: Additive manufacturing; Titanium; Phase transformation; Microstructure evolution; EBSD; Dissimilar alloy welds